2014
DOI: 10.3390/insects5010139
|View full text |Cite
|
Sign up to set email alerts
|

Common Virulence Factors and Tissue Targets of Entomopathogenic Bacteria for Biological Control of Lepidopteran Pests

Abstract: This review focuses on common insecticidal virulence factors from entomopathogenic bacteria with special emphasis on two insect pathogenic bacteria Photorhabdus (Proteobacteria: Enterobacteriaceae) and Bacillus (Firmicutes: Bacillaceae). Insect pathogenic bacteria of diverse taxonomic groups and phylogenetic origin have been shown to have striking similarities in the virulence factors they produce. It has been suggested that the detection of phage elements surrounding toxin genes, horizontal and lateral gene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 160 publications
0
39
0
Order By: Relevance
“…Notably, we identified Serratia , Lysinibacillus (formerly Bacillus ) and Pseudomonas , species of which have been reported to have entomopathogenic properties (Castagnola and Stock 2014). In addition, one sample had a high number of reads attributed to a relative of a non-bacterial entomopathogen, Metarhizium rileyi , which has been previously isolated and tested for efficiency against S. frugiperda (Maniania and Fargues 1985); Mallapur et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we identified Serratia , Lysinibacillus (formerly Bacillus ) and Pseudomonas , species of which have been reported to have entomopathogenic properties (Castagnola and Stock 2014). In addition, one sample had a high number of reads attributed to a relative of a non-bacterial entomopathogen, Metarhizium rileyi , which has been previously isolated and tested for efficiency against S. frugiperda (Maniania and Fargues 1985); Mallapur et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively less attention has been devoted to other important research aspects, such as the complex network of molecular interactions underpinning the host killing mechanism and the role of factors other than the pore-forming toxins that contribute to B. thuringiensis pathogenicity and virulence (20,21). A heated debate on the B. thuringiensis killing mechanism started almost a decade ago, and a consensus has not yet been reached.…”
mentioning
confidence: 99%
“…In the study, we used the leaf and stem-specific ST-LS1 promoter to make no cry3A gene expression in stems and tubers, which seems to be more favorable to the transgenic biosafety for food. Up to now, the transgenic crops have widely appeared in many countries, and many insect-resistant strains, such as rice, cotton, creeping bentgrass, tall fescue, Arabidopsis and Brachypodium distachyon have been planted in the laboratory and in greenhouses [48][49][50][51][52][53][54]. In this study, the results from inoculation with first-instar larvae on plants showed that larvae in some transgenic lines led to higher mortality, lower insect biomass accumulation and foliage consumption.…”
Section: Discussionmentioning
confidence: 89%